The Effect of Green Intellectual Capital, Green Accounting, and Firm Size on Financial Performance through ESG - Atarwaman, Rita JD (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Growing environmental sustainability concerns have intensified expectations for companies to integrate green practices and transparent ESG disclosure into their operations as a means of enhancing credibility and financial performance in increasingly sustainability-oriented capital markets. This research investigates the effects of green intellectual capital, green accounting, and firm size on financial performance, with ESG disclosure serving as a mediating variable. The study focuses on Indonesian publicly listed companies that are consistently included in the SRI-KEHATI Index and/or IDX ESG Leaders from 2018 to 2025. The data were analyzed quantitatively using the Partial Least Square (PLS) technique. The findings reveal that neither green intellectual capital nor green accounting significantly influences financial performance, measured by Return on Assets (ROA), while firm size demonstrates a significant positive impact. ESG disclosure also shows no significant direct effect on financial performance and is unable to mediate the relationships between green intellectual capital, green accounting, or firm size and financial performance. These results suggest that internal, environmentally oriented initiatives have yet to generate measurable short-term financial benefits without additional supporting factors. This study provides valuable insights for corporate decision-makers and stakeholders regarding the necessity of aligning sustainability practices with financial outcomes.